Highly Sensitive FBG Strain Sensor With Enhanced Measurement Range Based On Higher Order FWM - Chiranjit Ghosh; Vishnu Priye (IEEE Photonics Journal, 2020)
To meet the simultaneous requirement of high sensitivity and high measurement range is an uphill task in the development of fiber Bragg grating (FBG) strain sensor. A unique scheme of highly sensitive FBG strain sensor is proposed based on nonlinear four wave mixing (FWM) with a high measuring range. In this paper, both the edges of FBG reflection spectrum are used without increasing the number of sources. The FWM products generated are tuned to the reflection edges of the FBG. The signals reflected from the edges of the FBG are then utilized in the subsequent FWM process to enhance the sensitivity of the system. The proposed scheme can provide a strain measurement range of 2310 με with strain sensitivity of 91.21 dBm/nm.